LP-Sasakian Manifolds Equipped with Zamkovoy Connection and Conharmonic Curvature Tensor - Mandal, Abhijit; Das, Ashoke (Journal of the Indonesian Mathematical Society, 2021)
In this paper we have proved some results on conharmonically flat, quasi conharmonically flat and Ï†-conharmonically flat LP-Sasakian manifolds with respect to Zamkovoy connection. Also, we study generalized conharmonic Ï†-recurrent LP-Sasakian manifolds with respect to Zamkovoy connection. Moreover, we study LP-Sasakian manifolds satisfying K*(Î¾,U)âˆ˜R*=0, where K* denotes conharmonic curvature tensor and R* denotes Riemannian curvature tensor with respect to Zamkovoy connection.